Website-based food ordering information system for UMKM - Hendi Rahadiansyah; Lukman Junaedi (Jurnal Mantik, 2024)
This research aims to help MSMEs or Micro, Small and Medium Enterprises implement their business into digital, the author will examine GISAGIS.ID MSMEs with the topic "Designing a Website-Based Food Ordering Information System for MSMEs (GISAGIS.ID Case Study)". The research method applied in this research is the Waterfall method or commonly referred to as the SDLC or System Development Life Cycles approach. system development methods system analysis and feasibility testing. using needs analysis with several techniques, namely observation, interviews and literature studies in order to find out the details of the system needed.  Results of System Needs Assessment This stage is the result of analyzing the needs used to create a food ordering information system website at Gisagis UMKM. The next process is to create a website-based information system that uses UML or Unified Modeling Languange such as use case diagrams, activity diagrams and class diagrams. The results of the research that the authors conducted showed a change in the purchasing process because they experienced success in making applications for UMKM GISAGIS.ID to be more effective and efficient in the sales and purchasing process because of the supporting applications. So that this system does not stop to develop. In supporting a wider market, developing this food ordering information system on a mobile basis, both android and ios to be simpler in ordering food and can also be developed into a B2B digital business, for example such as a franchise